2013
DOI: 10.1107/s1744309113024676
|View full text |Cite
|
Sign up to set email alerts
|

Purification, crystallization and preliminary crystallographic analysis of the SpaA backbone-pilin subunit from probioticLactobacillus rhamnosusGG

Abstract: Lactobacillus rhamnosus GG, a widely used Gram-positive probiotic strain, is clinically well known for its perceived health-promoting effects. It has recently been shown to display proteinaceous pilus fibres (called SpaCBA) on its cell surface. Structurally, SpaCBA pili possess a characteristic three-pilin polymerized architecture, with repeating SpaA major pilins that form the backbone and two types of minor subunits (SpaB and SpaC). In this study, recombinant SpaA protein was purified, characterized and crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 13 publications
(12 reference statements)
1
19
0
Order By: Relevance
“…This was expected as bacterial adhesion to cellular surfaces is multifactorial and involves different specific and non-specific interactions between bacterial and cell surface components. Non-specific mechanisms involve electrostatic and hydrophobic interactions, whereas the specific mechanisms are related to surface molecules, such as outer membrane proteins (Frece et al, 2005; Chen et al, 2007; Johnson-Henry et al, 2007; Zhang et al, 2013; Meng et al, 2014), exopolysaccharides (EPSs, Lebeer et al, 2011), lipoteichoic acids (Granato et al, 1999), peptidoglycans (Van Tassell and Miller, 2011), glycosaminoglycans (Martin et al, 2013), flagella, and fimbriae (Singh et al, 2013). This complex scenario results in species-specific adhesion (Deepika and Charalampopoulos, 2010; Messaoudi et al, 2012; Verdenelli et al, 2014) and may be related to the differences observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…This was expected as bacterial adhesion to cellular surfaces is multifactorial and involves different specific and non-specific interactions between bacterial and cell surface components. Non-specific mechanisms involve electrostatic and hydrophobic interactions, whereas the specific mechanisms are related to surface molecules, such as outer membrane proteins (Frece et al, 2005; Chen et al, 2007; Johnson-Henry et al, 2007; Zhang et al, 2013; Meng et al, 2014), exopolysaccharides (EPSs, Lebeer et al, 2011), lipoteichoic acids (Granato et al, 1999), peptidoglycans (Van Tassell and Miller, 2011), glycosaminoglycans (Martin et al, 2013), flagella, and fimbriae (Singh et al, 2013). This complex scenario results in species-specific adhesion (Deepika and Charalampopoulos, 2010; Messaoudi et al, 2012; Verdenelli et al, 2014) and may be related to the differences observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular packing in the crystal resembles native pili, with each C‐terminus adjacent to a linking lysine of the next molecule. A backbone pilin, SpaA in SpaCBA pili from L. rhamnosus GG is also a two‐domain backbone pilin (unpublished data, ).…”
Section: Backbone Pilinsmentioning
confidence: 92%
“…Structural information of pilins in non‐pathogenic bacteria is yet to emerge. However, preliminary data is available for two backbone pilins, SpaA and SpaD . Like Spy0128, SpaA is a two‐domain pilin.…”
Section: Pilins From Non‐pathogenic Gram‐positive Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, a similar structural approach using the TG/SG motif would further contribute to understanding the docking details of sortases and their dedicated substrates in L. rhamnosus GG and other Gram-positive species. A recent report indicated that the structure of the SpaA pilin of L. rhamnosus GG is soon to be solved, bringing to light important data to support the present regulatory model (58).…”
Section: Discussionmentioning
confidence: 99%